Metabolic Profiling of Fermented Products of the Ethanolic Extract of Acanthopanax sessiliflorus Fruit and Evaluation of Its Immune Enhancement Effect in RAW 264.7 Macrophages and BV2 Microglia - Kwan-Woo Kim; Bo-Ram Choi; Woo-Cheol Shin; Jin-Kyu Jang; Young-Seob Lee; Dahye Yoon; Dae Young Lee (Antioxidants)
In this study, we sought to evaluate the potential availability of 30% ethanol extract of Acanthopanax sessiliflorus fruit (ASE) as a prebiotic and compare the immune enhancement effect of ASE and its fermented products, which were fermented with three probiotic bacteria, namely, Lactobacillus plantarum (ASE-LPF), Streptococcus thermophilus (ASE-STF), and Lactobacillus helveticus (ASE-LHF). RAW264.7 and BV2 cells were treated with various concentrations of ASE and its fermented products. The level of nitric oxide was evaluated using a Griess reagent, and the levels of inflammatory cytokines were determined through an enzyme-linked immunosorbent assay. Western blot analysis was employed to determine the expression of various proteins related to immune responses. Our results show that fermentation with ASE significantly improved the probiotic growth of S. thermophilus and L. helveticus. Compared with ASE, treatment with only ASE-LHF increased the level of nitric oxide. Compared with ASE, treatment with ASE-LHF augmented the expression of inducible nitric oxide synthase, cyclooxygenase-2, and the production of inflammatory cytokines. It was confirmed that these enhancement effects were due to the activation of the nuclear factor kappa B and extracellular signal-regulated kinase mitogen-activated protein kinase signaling pathways. Additionally, secondary metabolite profiling of ASE and its fermented products was performed using UPLC-QTOF/MS to identify ASE’s promising compounds. Through metabolomic analysis, 23 metabolites showing significant differences between ASE and its fermented products were compared. Therefore, this study demonstrates the possibility of ASE-LHF as a potential material for immune-enhancing agents.